2022
DOI: 10.3390/healthcare10101881
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Daily Life, Physical Activity, GAD, Depression, and Personal Hygiene of Adolescents in South Korea Due to the COVID-19

Abstract: This study used raw data obtained from the Adolescents’ Health Behavior Survey by government-affiliated agency open data. A total of 109,796 students were sampled. A comparative analysis was performed based on the year 2020 and when the COVID-19 pandemic occurred, in which we analyzed changes in adolescents’ depression and panic anxiety perception and dietary habits, physical factors, physical activity, and handwashing habits. There was no weight control in the second year compared to the first year of the COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A study conducted by Troiano's [59] team indicated that 42% of children aged 6-11 years in America met the recommended 60 min per day PA norm, whereas only 8% of adolescents reached this norm, and similar data were found in Australia [60]. Much research has estimated that students' decline in physical activity during the pandemic period was negatively associated with a lack of psychological wellbeing, depression, and sadness [49,61,62], which can indirectly lead to reduced academic performance [63,64].…”
Section: Discussionmentioning
confidence: 89%
“…A study conducted by Troiano's [59] team indicated that 42% of children aged 6-11 years in America met the recommended 60 min per day PA norm, whereas only 8% of adolescents reached this norm, and similar data were found in Australia [60]. Much research has estimated that students' decline in physical activity during the pandemic period was negatively associated with a lack of psychological wellbeing, depression, and sadness [49,61,62], which can indirectly lead to reduced academic performance [63,64].…”
Section: Discussionmentioning
confidence: 89%